PENGARUH GOOD CORPORATE GOVERNANCE DAN RASIO LIKUIDITAS TERHADAP FINANCIAL DISTRESS DIPERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2015-2018 - Fildan Khairuddin; Abdul Wahid Mahsuni; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT                                                                              This study aims to determine the influence of the board of directors, the proportion of independent commissioners, institutional ownership, managerial ownership, and liquidity ratios for financial distress in manufacturing companies listed on the Indonesia Stock Exchange 2015-2018. The number of 30 manufacturing companies taken by using purposive sampling technique is by selecting samples based on certain criteria. The data collection method used is the documentation method of collecting and recording secondary data in the form of financial statements at manufacturing companies listed on the Indonesia Stock Exchange. The data analysis technique used in this study is the normality test, multiple linear regression, classical assumption test. The results of the study injected that simultaneously the board of directors variable, the proportion of independent commissioners, institutional ownership, managerial ownership, and liquidity ratios had a significant effect on financial distress in manufacturing companies listed on the IDX. Partially the board of directors, the proportion of independent commissioners, institutional ownership, managerial ownership, and liquidity ratios have a negative and significant effect on financial distress in manufacturing companies listed on the IDX the results of this study can be used as information to change good corporate governance and liquidity ratios to financial difficulties in manufacturing companies listed on the Indonesia Stock Exchange (IDX).Keywords: good corporate governance, liquidity ratio, and financial dsitress.